Engineering a UV illumination device for decentralized autologous cancer immunotherapy - Endean, Delaney, author; Brennan-Pierce, Ellen, advisor; Parada, German, committee member (Colorado State University. Libraries, 2026)
Autologous cancer immunotherapy offers a promising approach to treatment by utilizing a patient's own tumor cells to stimulate an immune response; however, current implementations rely on cleanroom dependent transfer steps that limit accessibility and scalability. The Innocell process, developed by PhotonPharma, employs riboflavin and ultraviolet (UV) light to inactivate tumor cells while preserving their antigenic structure for personalized therapeutic use. This senior design project focused on the design and development of a benchtop UV illumination device incorporating a closed, single-use containment system to enable tumor cell inactivation within a sealed environment and eliminate open aseptic handling. Ultimately, the device will incorporate all steps of the Innocell process, including tissue dissociation, UV illumination, and final dose aliquoting. The system currently integrates controlled UV exposure and agitation while minimizing operator interaction to a single operational step, addressing risks associated with manual processing and contamination. The engineering approach emphasized iterative prototyping of containment systems, evaluation of material compatibility under UV exposure, and development of standard operating procedures (SOPs) for device operation, cell culturing, and analytical assays. A primary design challenge was achieving consistent and reliable sealing of the containment system, which limited the ability to produce a fully functional prototype and prevented completion of experimental validation. Despite this limitation, a comprehensive validation framework was established, including proposed burst testing for seal integrity, sterilization validation using biological indicators to confirm autoclave effectiveness, and computational fluid dynamics (CFD) analysis to assess mixing behavior and uniformity of UV exposure. These strategies were designed to quantify mechanical performance, sterility assurance, and treatment consistency within the system. Overall, this work demonstrates both the feasibility and key engineering challenges associated with developing a closed-system, decentralized immunotherapy device, highlighting the critical roles of manufacturability, material behavior, and seal reliability in advancing accessible autologous cancer treatment technologies.
Keywords: immunotherapy; UV illumination; engineering; autologous; riboflavin